"I Did What I Do" Versus "I Cover Football": Boundary work, in-house media and athlete protest. (16th March 2018) - Mirer, Michael
Abstract : As athletes added their voices to the fall 2014 protests against police violence, in-house reporters, that is, content producers paid to produce stories for team websites, were part of the press pack describing these actions. Despite working for teams, many view themselves as sports journalists, despite working for teams, view themselves as sports journalists. This collision of sports and politics posed a challenge to the professional identities they try to maintain. Using interview data and textual analysis, this case study examines the ways that in-house sportswriters understood and operationalized their professional identities at a moment when they came into potential conflict with their employment situations. Their answers reflect boundary work on the part of in-house media members, who stressed their independence and news judgment in explaining their choices around this story even if their actions diverged. The work raises questions for understanding how journalistic identity translates to new contexts such as brand publishing.